2008
DOI: 10.1128/mcb.02252-07
|View full text |Cite
|
Sign up to set email alerts
|

GTPase-Mediated Regulation of the Unfolded Protein Response in Caenorhabditis elegans Is Dependent on the AAA+ ATPase CDC-48

Abstract: When endoplasmic reticulum (ER) homeostasis is perturbed, an adaptive mechanism is triggered and named the unfolded protein response (UPR). Thus far, three known UPR signaling branches (IRE-1, PERK, and ATF-6) mediate the reestablishment of ER functions but can also lead to apoptosis if ER stress is not alleviated. However, the understanding of the molecular mechanisms integrating the UPR to other ER functions, such as membrane traffic or endomembrane signaling, remains incomplete. We consequently sought to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 48 publications
4
47
0
Order By: Relevance
“…4). This is in agreement with data showing that RhoA is involved in the SPARC-induced migration of U87 cells (Kunigal et al, 2006) and is consistent with our previous work linking Rho GTPase signaling to the Unfolded Protein Response (Bouchecareilh et al, 2011b;Caruso et al, 2008). Moreover, SPARC expression has been previously described to increase U87 cell migration (Rempel et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…4). This is in agreement with data showing that RhoA is involved in the SPARC-induced migration of U87 cells (Kunigal et al, 2006) and is consistent with our previous work linking Rho GTPase signaling to the Unfolded Protein Response (Bouchecareilh et al, 2011b;Caruso et al, 2008). Moreover, SPARC expression has been previously described to increase U87 cell migration (Rempel et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…S4), indicating a narrow range of concentrations conferring beneficial effects. Expression of two sensors of UPR induction, hsp-4p::GFP and ckb-2p::GFP (20,24) at TM concentrations as low as 0.1 μg/mL confirmed that preconditioning induces the UPR (Fig. 4C).…”
Section: Hpl-2 Plays Opposing Functions In the Intestine And Neuronalmentioning
confidence: 61%
“…At present it is unclear how CDC-48 affects replication but recent studies reported that p97 binds to DNA replication factors (31,32). Interestingly, p97 associates with the human Werner RecQ helicase (33) and C. elegans CDC-48.1 with HIM-6, a Bloom Syndrome helicase homolog (34). As both RecQ helicases are involved in DNA replication to prevent accelerated aging, it is conceivable to speculate about an evolutionarily conserved requirement of CDC-48/p97 in DNA synthesis linked to cancer and longevity.…”
Section: Resultsmentioning
confidence: 99%